2018
DOI: 10.1111/jeb.13304
|View full text |Cite
|
Sign up to set email alerts
|

Divergent parasite infections in sympatric cichlid species in Lake Victoria

Abstract: Parasitism has been proposed as a factor in host speciation, as an agent affecting coexistence of host species in species-rich communities and as a driver of post-speciation diversification. Young adaptive radiations of closely related host species of varying ecological and genomic differentiation provide interesting opportunities to explore interactions between patterns of parasitism, divergence and coexistence of sympatric host species. Here, we explored patterns in ectoparasitism in a community of 16 fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…In our previous studies, we found that populations of Pundamilia with intermediate differentiation, inhabiting Kissenda and Python Islands, showed some infection divergence (Gobbin et al in prep.). In the wild, P. nye are more frequently infected, and in higher numbers, with L. monodi and E. lamellifer than P. pun (Maan et al, 2008;Karvonen et al, 2018;Gobbin et al, 2020). Here, we report that these differences were absent in fish raised in the laboratory, where the expression of species-specific depth and diet Fig.…”
Section: Species Differences In Infectionmentioning
confidence: 52%
See 3 more Smart Citations
“…In our previous studies, we found that populations of Pundamilia with intermediate differentiation, inhabiting Kissenda and Python Islands, showed some infection divergence (Gobbin et al in prep.). In the wild, P. nye are more frequently infected, and in higher numbers, with L. monodi and E. lamellifer than P. pun (Maan et al, 2008;Karvonen et al, 2018;Gobbin et al, 2020). Here, we report that these differences were absent in fish raised in the laboratory, where the expression of species-specific depth and diet Fig.…”
Section: Species Differences In Infectionmentioning
confidence: 52%
“…In nature, these two species are sympatric but differ in their average depth distribution and diet. Previous studies in this species pair, as well as in closely related populations inhabiting other locations in Lake Victoria, revealed that they differ in parasite infection (Maan et al, 2008;Karvonen et al, 2018;Gobbin et al in prep.). They mate assortatively, mediated by species-specific female preferences for male coloration (blue vs. red; Seehausen & van Alphen, 1998.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In Lake Malawi alone, there are over 500 species of cichlids, inhabiting a diversity of environmental and feeding niches. Cichlid species exhibit a high degree of habitat fidelity and partition their environment along discrete ecological axes, including distinct biotic (food availability, predation, and parasites) and abiotic (light, water chemistry) environments that play a critical role in the origins and maintenance of cichlid biodiversity [12][13][14][15][16][17]. Predation on Malawi cichlids is considered to be relatively low, which is thought to have contributed to their evolutionary and ecological success [18].…”
Section: Introductionmentioning
confidence: 99%